π-Shaped Lymphaticovenular Anastomosis: The Venous Flow Sparing Technique for the Treatment of Peripheral Lymphedema - Ayestaray, Benoit; Bekara, Farid (Journal of Reconstructive Microsurgery, 2014)
Background Nowadays, lymphaticovenular anastomosis has been recognized as an efficient microsurgical treatment for peripheral lymphedema. The technique based on two end-to-side anastomosis is named π-shaped lymphaticovenular anastomosis. This is the venous flow-sparing technique, in which the distal endothelial cells are not sacrificed. The purpose of this study is to evaluate the clinical results of π-shaped lymphaticovenular anastomosis in chronic lymphedema of the upper and lower limbs.Patients and Methods From November 2010 to August 2011, 20 patients with a peripheral lymphedema were treated by π-shaped lymphaticovenular anastomosis. A total of 12 patients had a lymphedema of the upper limb and 8 patients had a lymphedema of the lower limb. The mean age of the patients was 57.2 years (range, 44–78 years). The mean duration of lymphedema was 6.2 years (range, 1–23 years). The Campisi clinical stage range 2 to 5 (average, 3.3). Every patient was operated under local anesthesia. Four π-shaped lymphaticovenular anastomoses were performed per limb.Results The mean caliber of lymphatic vessels used for lymphaticovenular anastomosis was 0.55 mm (range, 0.3–0.8 mm). The mean caliber of subdermal venules was 1.2 mm (range, 0.5–2.1 mm).The average operative time to perform one π-shaped lymphaticovenular anastomosis was 55 minutes (range, 45–65 minutes). A venous backflow was found in 98 lymphaticovenular anastomosis (55.7%). Total 16 patients (80%) had a clinically significant circumferential reduction after surgery. The average volume differential reduction rate was 22.9% (range, 4.9–46.3) (p < 0.001).Conclusions π-Shaped lymphaticovenular anastomosis is a supermicrosurgical method with a low morbidity to treat peripheral lymphedema. The procedure can easily be performed under local anesthesia, and the postoperative recovery is short. The results of this series demonstrate a clinical efficiency of the technique to reduce chronic lymphedema of the limbs.EBM level IV.
Keywords: lymphedema; venous flow sparing lymphaticovenular anastomosis; end-to-side